JIMMY SMITH’S STRUGGLE TO BE ACCEPTED BY BLACK RAPPER COMMUNITY IN 8 MILE MOVIE - INDRAWANTOKO, BAGUS (Jurnal Ilmiah Mahasiswa FIB, 2013)
Rap music is one of genre music which is pioneered by Black people. Black people play an important role in rap music. Even, almost all of rap musicians are Black people. But, this condition does not make Jimmy Smith’s character as White American become pessimist to be a talented rapper. Jimmy knows what he must to do to be a rapper and struggle in gaining his dream. To study this movie, sociological approach is used. The result of the study showed that White American like Jimmy Smith’s character must adapt himself in Black’s environment especially in Black’s rapper community. In 8 Mile movie, Jimmy as White American’s character, does some hard struggles to gaining his dream become a talented rapper. In his struggle’s, Jimmy gets unusual treatment like discrimination from Black people who become a major in rap music.